2019
DOI: 10.1371/journal.pone.0226698
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome reveals the potential modulation mechanisms of estradiol affecting ovarian development of female Portunus trituberculatus

Abstract: Estradiol is an important sex steroid hormone that is involved in the regulation of crustacean ovarian development. However, the molecular regulatory mechanisms of estradiol on ovarian development are largely unknown. This study performed transcriptome sequencing of ovary, hepatopancreas, brain ganglion, eyestalk, and mandibular organ of crabs after estradiol treatment (0.1μg g-1 crab weight). A total of 23, 806 genes were annotated, and 316, 1300, 669, 142, 383 genes were expressed differently in ovary, hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 92 publications
1
11
0
Order By: Relevance
“…In addition, significant expression of Wnt5b was observed in the ovaries, and it was significantly higher than that in the testes. These results indicated that Wnt5b is involved in the development of the reproductive system (testes and ovaries), which is consistent with previous reports in Muscovy ducks, swimming crab, and common carp (Liu et al, 2019; Bai et al, 2020; Deepa and Senthilkumaran, 2021). Notably, in adult carp, high expression levels of Wnt5b were observed in both testes and ovaries, indicating the functional differences of Wnt5b gene among different species.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, significant expression of Wnt5b was observed in the ovaries, and it was significantly higher than that in the testes. These results indicated that Wnt5b is involved in the development of the reproductive system (testes and ovaries), which is consistent with previous reports in Muscovy ducks, swimming crab, and common carp (Liu et al, 2019; Bai et al, 2020; Deepa and Senthilkumaran, 2021). Notably, in adult carp, high expression levels of Wnt5b were observed in both testes and ovaries, indicating the functional differences of Wnt5b gene among different species.…”
Section: Discussionsupporting
confidence: 92%
“…The presence of hormones, particularly the vertebrate-type steroids such as progesterone (Pg) and estradiol (E 2 ) hormones, have been reported in the hepatopancreas, ovary, and hemolymph of Chinese white shrimp Penaeus chinensis [7], green mud crab Scylla serrata [8], blue pearl crayfish Cherax albidus [9], narrow-clawed crayfish Astacus leptodactylus [10], and swimming crab Portunus trituberculatus [6]. In general, E 2 and Pg play a vital role in crustacean reproduction via enhancing the initiation of related metabolic pathways during vitellogenesis [11,12], but their concentrations with ovarian maturation stages vary between species. Interestingly, the changes in the vertebrate type of steroids titer during oocyte maturation indicate their importance in governing the vitellogenesis process, which involves the mobilization of lipids from the storage sites [13].…”
Section: Introductionmentioning
confidence: 99%
“…We also note that steroid hormones previously described in crustaceans include ecdysteroids, which play an essential role in regulating the molting cycle, as well as vertebrate-type steroids such as estrogen and progesterone which fulfil functions in vitellogenesis and ovarian development (Lafont and Mathieu 2007, Liu et al . 2019, Nakagawa and Henrich 2009).…”
Section: Discussionmentioning
confidence: 92%